2014
DOI: 10.1038/cmi.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 acts as a promising therapeutic target in systemic lupus erythematosus by regulating plasma cell differentiation

Abstract: Plasma cells, which secrete auto-antibodies, are considered to be the arch-criminal of autoimmune diseases such as systemic lupus erythematosus, but there are many cytokines involved in inducing the differentiation of B-cell subsets into plasma cells. Here, we emphasize IL-21, which has emerged as the most potent inducer of plasma cell differentiation. In this review, we focused on the promoting effects of IL-21 on plasma cell differentiation and discuss how these effects contribute to B cell-mediated autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…21 However, the role of IL-21 in regulating human CXCR4 expression in autoimmunity has not been examined to date. IL-21, which is mainly produced by activated CD4 + T and T FH cells, is essential in regulating B cell responsiveness, 25,[32][33][34] and has been suggested that IL-21 might serve as a therapeutic target in lupus. 35 As demonstrated in our study, SLE B cells expressed higher levels of IL-21R than HC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, the role of IL-21 in regulating human CXCR4 expression in autoimmunity has not been examined to date. IL-21, which is mainly produced by activated CD4 + T and T FH cells, is essential in regulating B cell responsiveness, 25,[32][33][34] and has been suggested that IL-21 might serve as a therapeutic target in lupus. 35 As demonstrated in our study, SLE B cells expressed higher levels of IL-21R than HC.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 IL-21, produced mainly by follicular helper T cells (T FH ), which have a central role in GC B-cell selection, is able to directly induce B-cell activation, mediate B-cell proliferation and promote plasma cell development, most likely through the downstream pathway of the Janus kinase/Signal transducer and activator of transcription (JAK/STAT) signaling. 25 Furthermore, a recent study indicated that phosphatidylinositol 3 kinase (PI3K)/Akt may be involved in CXCR4 regulation. 26 Thus, the JAK/STAT and PI3K/Akt pathways are involved in many physical and pathological activities.…”
Section: Introductionmentioning
confidence: 99%
“…12 IL-21, a wellknown signature factor of follicular helper T cells, is a pleiotropic cytokine that can influence the activation, differentiation, and expansion of germinal center B cells and is critically involved in the pathogenesis of SLE. [13][14][15] It has been reported that MRL/lpr mice develop lupus-like disease in an IL-21-dependent manner. 16 Collectively, IL-6, IL-10 and IL-21, which are pro-inflammatory mediators in humoral immunity, are regarded as biomarkers of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Increased numbers of TFH and its association with autoantibody production have been reported in SLE patients and mice [117][118][119]. IL-21, as one of the signature molecules of TFH, is up-regulated in SLE and leads to expansion of TFH [120][121][122]. But the precise mechanism that expanded TFH leading to release of autoreacive B cells is not clear.…”
Section: B Cell Tolerance Checkpointsmentioning
confidence: 99%
“…IL-21 is an essential cytokine to co-stimulate B cells differentiating into plasma cells [122,145]. IL-21 is mainly produced by TFH in GC and TFH is essential for GC B cells selection [146,147].…”
Section: Other Cytokinesmentioning
confidence: 99%